Effect of Utilitarian Benefit on Green Brand Equity with Green Brand Image - Ian Nurpatria Suryawan (Jurnal Manajemen, 2019)
The concept of Green Brand Equity (GBE) is a benchmark in determining the degree of value accumulated by green brands based on the function of green products. Many people use mineral water that is taken directly from the packaging and realize to use environmentally friendly mineral water packaging. The packaging must be easily recycled. Results shows Utilitarian Benefit (UB) has a positive effect on Green Brand Equity (GBE) mediated by Green Brand Image (GBI) based on Gender, which men and women have almost concerning for environment friendly packaging. The reason is the environment damage such as environmental pollution includes water pollution, air pollution, environmental damage eg.forest damage, erosion that causes flooding, damage to coral reefs to global warming. The effectiveness of Green Brand Equity (GBE) enhance Green Brand Image (GBI) and brand loyalty including insight environmentally friendly packaging is important to keep the safe environment